Zero sets of entire absolutely monotonic functions - Katkova, O.; Vishnyakova, A. (My University, 2001)
The paper is devoted to the problem of characterization of the class of subsets of $\mathbb {C}$ which can serve as zero sets of entire absolutely monotonic functions.
Keywords: entire absolutely monotonic function; zero set of entire function